Monsoon in são paulo state, brazil - Machado, Antonio Jaschke [UNESP] (Revista Brasileira de Geografia Fisica, 2019)
This paper corroborates the existence of monsoon in São Paulo, revealed from the observation of periodic fluctuations in absolute humidity. The daily cycle and the seasonal cycle recorded in two sites in the eastern and western extremes of São Paulo are compared and analyzed. The incorporation of the wind direction to the analysis suggests the existence of a monsoon regime, whose transition between the wet season and the dry season is defined by the variation of the absolute humidity.
Monção em São Paulo, Brasil
Keywords: Absolute humidity; Monsoon; Wind direction